Evaluation of the Updating of the Permanent Voter List (DPT) in the 2024 Regional Election of Surabaya in Wonokromo District - Muhammad Kholilur Rahman; Suci Megawati; Indah Prabawati; Fierre An Suprapto (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study evaluates the preparation of the voter list for the 2024 Surabaya City Pilkada in Wonokromo District based on PKPU Number 7 of 2024. Problems found include inaccurate DP4, deceased voter data (TMS 1), duplicate data, coordination constraints, and disruptions to the e-coklit system. This study uses a qualitative descriptive method through interviews, literature studies, and documentation with the CIPP (Context, Input, Process, Product) model approach. The results of the study indicate the following: 1) Context evaluation reveals socio-economic barriers in the form of reluctance to report deaths in order to maintain social assistance and limited access in elite areas. 2) Input evaluation reveals that organizers are able to adapt despite technical limitations. 3) The evaluation of the success process is supported by effective factual verification and cross-sectoral synergy. 4) Product evaluation reveals voter data validity of 90–95% and effective and integrated TMS data cleaning. Research recommendations include: 1) Context evaluation strengthens DP4 data synchronization between institutions, improves field coordination, and harmonizes election and social policies. 2) Evaluation of input to improve the quality and duration of practice-based Pantarlih technical guidance, optimization of the e-coklit application. 3) Evaluation of products to strengthen human resource competency and integrity based on SIMP principles, accompanied by improvements in the welfare of organizers and supervisors.